Pengaruh Kompetensi Kerja dan Komitmen Organisasi Terhadap Kinerja Guru Dimediasi Motivasi Berprestasi pada Sekolah Dasar Negeri 47 Kota Jambi - Armawati, Yulis; Rosita, Sry; Fazri, Andang (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to describe the competency, organizational commitment, achievement motivation and performance of teachers at State Elementary School 47 in Jambi City, as well as examining the influence of competency and organizational commitment on teacher performance both directly and indirectly through achievement motivation. The unit of analysis for this research is the 47th State Elementary School in Jambi City with a population of 52 teachers. The research uses a quantitative approach with survey methods and uses Partial Least Square (PLS) data analysis. The research results show that competence directly or indirectly through achievement motivation has a positive and significant influence on teacher performance. Then organizational commitment only has a direct influence on teacher performance, while indirectly through motivation it does not have a significant influence on teacher performance